Respostas

2014-05-05T23:29:02-03:00
A) x = 2 ⇒ r = 3*2 - 12 ⇒ r= 6 - 12 ⇒  r = -6

b) x=-3  ⇒    r = 3 * (-3) - 12  ⇒ r = -9-12 ⇒ r = -21

c) x= -9 ⇒   r = 3 * (-9) - 12 ⇒ r = -27 -12 ⇒   r = - 39

d) x=10 ⇒  r = 3* 10 - 12 ⇒   r=30-12 ⇒  r =18

e) x=0 ⇒ r = 3 * 0 -12 ⇒ r= 0-12 ⇒ r = -12

f) x= - 6⇒  r = 3* (-6) ⇒ r =-18 -12 ⇒ r = - 30

Espero ter ajudado !
2014-05-05T23:31:25-03:00
Vamos lá:

A) x = 2
   r = 3 . 2 - 12
   r = 6 - 12
   r = - 6

B) x = - 3
    r = 3 . (- 3) - 12
    r = - 9 - 12
    r = - 21

C) x = - 9
    r = 3 . (- 9) - 12
    r = - 27 - 12
    r = - 39

D) x = 10
    
r = 3 . 10 - 12
    r = 30 - 12
    r = 18

E) x = 0
    r = 3 . 0 - 12
    r = - 12

F) x = - 6
    r = 3 . (- 6) - 12
    r = - 30

Espero ter ajudado. Valeu!